Supporting farmer participation in formal seed systems: lessons from Tharaka, Kenya. Issue 2 (17th February 2016) - Mucioki, Megan; Hickey, Gordon M.; Muhammad, Lutta; Johns, Timothy
ABSTRACT: This article examines contemporary challenges of formal seed sector participation for resource-poor farmers in Tharaka and engages in a wider discussion of national seed policy and formal seed sector development in Kenya. While many farmers reported utilising modern seed varieties developed by the formal seed sector, the majority of these were introduced through seed aid and maintained through seed saving, supporting seed system integration strategies. Building on these findings, the article discusses ways in which national seed policy in Kenya might be refined to better meet national and regional development goals focused on decreasing the incidence of hunger and poverty.